Polytechnic Education and Its Possible Use at Non-Technical Secondary School - KLEMENT, MILAN (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2017)
Technological and polytechnic education in the field of computer aided design (drafting) in 2D and 3D at non-technical secondary schools represents a new and relatively unexplored area. It is therefore necessary to deal with questions concerning the necessity of such training, and its potential influence and/or impact on students` further development. The answers were sought via an investigative research, the outcomes of which are presented by the submitted paper.